Measuring Ethiopian farmers’ vulnerability to climate change across regional states - Deressa, T.T.; Hassan, R.M.; Ringler, Claudia (International Food Policy Research Institute, 2008)
Ethiopia’s agricultural sector, which is dominated by smallscale, mixed crop, and livestock farming, is the mainstay of the country’s economy. It constitutes more than half the nation’s gross domestic product (GDP), generates more than 85 percent of the foreign exchange earnings, and employs about 80 percent of the population. Ethiopia’s dependence on agriculture makes the country particularly vulnerable to the adverse impacts of climate change on crop and livestock production. This brief is based on a paper that analyzes the vulnerability of Ethiopian farmers to climate change by creating a vulnerability index and comparing vulnerability indicators across regions. A regional vulnerability index can assist in identifying the areas of Ethiopia that are most vulnerable to climate change and guide policymakers in determining where investments in adaptation may be most effective in reducing the future adverse effects of climate change.